PSV-1 A prospective longitudinal study of the incidence and risk factors associated with footrot in feedlot lambs in Southern Alberta - Schwartzkopf-Genswein, Karen S (J Anim Sci, 2020)
Lameness in sheep caused by footrot (FR) is a significant health, welfare, and economic concern worldwide. To date, no studies have documented the incidence of FR or associated risk factors in feedlot lambs in Alberta. The objectives of this study were to determine 1) FR incidence and 2) animal, managerial and environmental risk factors associated with FR in one Southern Alberta, lamb feedlot. Assessments were conducted biweekly (average of 10 pens per visit) by 2 experienced observers. A total of 73,150 lambs were assessed between October 2017 and March 2019. All lame lambs were scored according to a 3-point mobility scale (1 = mild, 2 = moderate, and 3 = severe lameness) and physically examined to diagnose the cause of lameness. Risk factors associated with FR were documented and included gender, days on feed (DOF), diet composition, and season. Multivariable regression models (SAS PROC GLIMMIX) were used to determine significant risk factors. A total of 473 lambs were identified as lame, 107 of which were diagnosed with FR (incidence of 22.6%). Footrot affected lambs had greater mobility scores (≥ 2; P < 0.0001) than all other lame diagnoses. Footrot was 4.40 and 0.10 times more likely (P < 0.0001) in female and wether than ram lambs, and 0.60 and 0.23 times more likely (P < 0.0001) in fall and summer than winter and spring seasons. The odds of being diagnosed with FR increased for each additional DOF and each unit increase of barley in the diet (P = 0.0268), while the odds decreased (P = 0.0016) for each additional unit of supplement in the diet. Based on our findings, footrot is an issue to lambs in Alberta, and further studies are still necessary to understand the risk factors associated with potential strategy for mitigating FR in feedlot lambs.